To Belabour The Points: Encoding Vowel Phonology in Syriac and Hebrew Vocalization. (20th February 2021) - Posegay, Nick
Abstract: Medieval Hebrew and Syriac scribes both indicated vowels by placing dots above or below their consonantal writing. These vowel points were created in the Late Antique and early Islamic periods to disam-biguate the vocalization of important texts, especially the Bible. The earliest step in this process was the implementation of the Syriac 'diacritic dot' system, which used a single dot to distinguish pairs of homographs: a dot 'above' marked a word with relatively-backed vowels, and a dot 'below' marked its homograph with relatively-fronted vowels. This graphic depiction conveyed a phonological association of 'height' with 'backness', and that association then entered the Maso-retic Hebrew tradition in the form of mille'el ('above') and millera' ('below') homograph comparisons. In turn, this principle of backness as 'height' informed the later placement of both the Syriac and the Tiberian Hebrew vowel points. 1